UNDERSTANDING THE DIFFERENT APPROACHES OF INTERNATIONAL ARBITRATION GRAPPLED WITH CORRUPTION ISSUES - Tsabitah, Tsany Ariqah (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2022)
Corruption has been a challenge in most countries in the world and also internationally. Many cases of international contracts are procured or allegedly procured by corruption. International legal instruments nowadays try to combat this issue and the application further needs to be followed to the international arbitration for dispute resolution. The problem of corruption is more systematic, hard, and needs extra time to be sure. The next problem that has to be discussed in this article is the dispute resolution field in arbitration about the agreement or contracts allegedly procured by corruption. The implication of alleged corruption has broadly changed the arbitration proceeding and its capacity to adjudicate this issue. This article examines judicial-normative explains what approaches have been used and the development of facing the corruption issues in international arbitration and the effects on the proceeding finding the difference between investment to commercial arbitration from case to case.